ANALISIS KINERJA KEUANGAN PERUSAHAAN SEKTOR PERDAGANGAN, JASA, DAN INVESTASI SEBELUM DAN SESUDAH GO PUBLIC PADA BURSA EFEK INDONESIA - Jaka Anggara; Nizwan Zukhri; Dony Yanuar, S.E., M.M. (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The purpose of this research is to analyze the financial performance of companies in the trade, services, and investment sectors before and after going public on the Indonesia Stock Exchange. The population for this study was obtained using probability sampling method from companies in the trade, services, and investment sectors that went public and were listed on the Indonesia Stock Exchange in the year 2018. Based on predetermined criteria, a sample of 8 companies in the trade, services, and investment sectors was obtained. The results of the financial ratio analysis for companies in the trade, services, and investment sectors before and after going public show that their financial performance is generally positive, albeit experiencing a decline in the second year. The test results indicate that there is no significant difference in liquidity, profitability, and activity ratios in the financial performance of companies in the trade, services, and investment sectors before and after going public. However, there is a significant difference in the solvency ratio.